(untitled) - Ayres, Clarence Edwin (Clifton, 1973)
This book introduce about the by-producs of invention. Science presents apologies. Science takes command...
Keywords: Science,Religion and science,Khoa học,Khoa học và tôn giáo; Philosophy,Triết học